### What is the Value of this Equation x2+(y-3√2x)2=1

**Answer:**

**Given Equation is **x^{2}+(y-3√2x)^{2}=1

Now Subtract X^{2 }from both sides of the equation (Means is that minus X^{2} from LHS and RHS side)

(y-3√2x)^{2}+x^{2}-x^{2}=1-x^{2}

Subtracting x^{2} from itself leave 0

(y-3√2x)^{2}=1-x^{2}

Now take square root of both sides of equation

**√**(y-3√2x)^{2}=√1-x^{2}

The square root operation always results is one positive number and one negative number.

(y-3√2x)=√1-x^{2}

(y-3√2x)=-√1-x^{2}

now take-3√2x from the right side then the value of is : y=√1-x^{2}+3√2x and y=-√1-x^{2}+3√2x

Hance: Value of This Equation is

## What is the Graph of x^2+(y-3√x^2)^2=1 ?

## x2+(y-3√x2)2=1 Meaning

The equation x^2 + (y – 3√x^2)^2 = 1 represents a certain geometric figure called an ellipse.

*Here is meaning of x2+(y-3√x2)2=1*

#### x^2 and (y – 3√x^2)^2:

These terms represent the squared distances from the center of the ellipse to the points on the curve along the x-axis and y-axis, respectively. However, the presence of the term 3√x^2 in the y term indicates a shift and scaling compared to the standard ellipse equation.

#### = 1:

This equation defines a limit for all points that fulfill the condition. These points form a closed curve, namely the ellipse.